A novel strategy of water-based synthesis method of zeolitic-imidazolate framework-14 (ZIF-14) - Kiki Maesaroh; Ghefira Iftina Zahra; Apang Djafar Shieddieque; Muhamad Diki Permana; Irkham; Rudiawan Edwin; Joddy Arya Laksmono; Diana Rakhmawaty Eddy; Iman Rahayu (Results in Chemistry)
This study report outlines a water-based rapid method for synthesizing zeolitic-imidazolate framework-14 (ZIF-14) at room temperature. ZIF-14 crystals were prepared by the reaction of 2-eim, zinc nitrate, and cetyltrimethylammonium bromide (CTAB) in deionized water. The physicochemical analysis showed that ZIF-14 synthesized by this method has a coordination bond between Zn and N from FTIR analysis, which was also confirmed by XPS analysis. XRD analysis showed that the structure of ZIF-14 is a pure phase with analcime (ANA) topology. In addition, SEM and TEM images show that ZIF-14 has a cubic shape. In addition, thermal and surface analysis showed that ZIF-14 has a specific surface area of 429.518 m2/g, an average pore volume of 0.5676 cm3/g, and an average pore radius of 26.43 Å, with a thermal stability of up to 440 °C. Therefore, ZIF-14 synthesized by this method has a potential application as a catalyst and gas separation.